INFLUENCES ON BRAND LOYALTY AMONG THAI FEMALE COSMETIC CONSUMERS - Taghipour, Amirhossein; Loh, Aaron (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to examine and identify variables and factors which influence Thai women’s purchasing decision of Korean cosmetics. The data were compiled from questionnaires given to 400 female respondents living in Bangkok, who were between the ages of 14-30 and who had purchased Korean cosmetics in the past.The methodology used in this study is the correlation coefficient relationship and ANOVA to test the hypotheses. The results illustrated that the country of origin COO has a relationship with the perceived quality of the cosmetics and consequently, to brand equity.There are differences between packaging, price, and perceived quality for customers, in which packaging has more influence on satisfaction. In addition, customer loyalty was affected indifferently by brand equity and customer satisfaction.